Clothing and Export Diversification : Still a Route to Growth for Low-Income Countries? - Brenton, Paul (World Bank, Washington, DC, 2012)
Can the clothing sector be a driver of export diversification and growth for today's low-income countries as it was in the past for countries that have graduated into middle income? This paper assesses this issue taking into account key changes to the market for clothing: the emergence of India and especially China as exporting countries; the rise of global production chains; the removal of quotas from the global trading regime but the continued presence of high tariffs and substantial trade preferences; the increasing importance of large buyers in developed countries and their concerns regarding risk and reputation; and the increasing importance of time in defining sourcing decisions. To assess the importance of the factors shaping the global clothing market, the authors estimate a gravity model to explain jointly the propensity to export clothing and the magnitude of exports from developing countries to the E U and US markets. This analysis identifies the quality of governance as an important determinant of sourcing decisions and that there appears to be a general bias against sourcing apparel from African countries, which is only partially overcome by trade preferences.